Selective electrodialysis device and application thereof

By improving the selective electrodialysis device, the membrane charge density is increased by using porous micro- and nanomaterials and organic framework catalytic materials to inhibit ion reverse migration, thus solving the problems of low separation rate and current efficiency of existing devices and achieving stable and efficient separation of monovalent and multivalent ions.

CN121490577AActive Publication Date: 2026-02-10HANGZHOU WATER TREATMENT TECH DEV CENT
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202610036762.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-13
Publication Date
2026-02-10
Estimated Expiration
2046-01-13

AI Technical Summary

Technical Problem

Existing selective electrodialysis devices have low separation rates when separating monovalent and polyvalent ions, low current efficiency, and are susceptible to contaminants, leading to unstable operation and increased power consumption.

Method used

Improved cation exchange membranes and anion exchange membranes are used, coated with porous micro/nano materials and organic framework catalytic materials to increase membrane charge density, promote ion migration, and inhibit ion reverse migration through a barrier layer. At the same time, a pre-filter is set to remove pollutants.

Benefits of technology

It improves the separation rate and current efficiency of monovalent and multivalent ions, stabilizes operation, reduces power consumption, and effectively prevents fouling and scaling, achieving highly efficient lithium and magnesium ion separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121490577A_ABST
    Figure CN121490577A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment equipment and application, and particularly relates to a selective electrodialysis device and application thereof. The selective electrodialysis device comprises an electrodialysis tank, an anode and a cathode are respectively arranged on two sides of the electrodialysis tank, and a cation exchange membrane and an anion exchange membrane are sequentially arranged between the anode and the cathode; wherein the cation exchange membrane takes sulfonated polybenzimidazole as a base material, and the surface of the cation exchange membrane is coated with sodium polystyrenesulfonate containing a porous micro-nano material; one surface, facing the anode, of the cation exchange membrane is coated with a protective layer containing polybiphenylpiperidine; the anion exchange membrane takes quaternized polysulfone or polyether sulfone as a base material, and the surface of the anion exchange membrane is coated with poly dimethyl diallyl ammonium chloride. The device can efficiently separate monovalent ions and multivalent ions, functionalizes the ion exchange membrane to increase the charge density of the membrane, promotes rapid migration of the ions under the action of an electric field, improves the ion transfer rate, is stable in operation, and has relatively high separation rate and current efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a selective electrodialysis device and its application, belonging to the field of water treatment equipment and application technology. Background Technology

[0002] Membrane separation offers advantages such as high separation efficiency, simple operation, low energy consumption, and no secondary pollution. Selective electrodialysis, in particular, can effectively separate monovalent and multivalent ions. For example, patent application CN115448429A discloses a monovalent selective bipolar membrane electrodialysis device and a method for treating high-salinity wastewater. This method reveals that under the influence of an electric field, ions in high-salinity wastewater undergo directional migration. Due to electrostatic repulsion, monovalent Cl- ions... - It preferentially enters the cation exchange fiber network and passes through the monovalent selective anion exchange membrane into the acid chamber on the cation side of the bipolar membrane, where it reacts with the H2 produced by the hydrolysis of the bipolar membrane. + Finally, it flows out as a solution of HCl with a certain concentration; monovalent Na + Ions preferentially enter the anion exchange fiber network and pass through the monovalent selective cation exchange membrane into the anion-side alkaline chamber of the bipolar membrane, where they react with OH- generated by the hydrolysis of the bipolar membrane. - Finally, it flows out as a NaOH solution of a certain concentration; due to the electrostatic repulsion of the anion and cation exchange fiber network and the dual retention effect of the monovalent selective ion exchange membrane, SO4 in the high-salt wastewater is effectively removed. 2- CO3 2- Divalent anions, and a small amount of Ca remaining after softening. 2+ Mg 2+ High-valence cations are retained in the salt chamber, thus greatly improving the purity of HCl and NaOH solutions; however, they can only be used to separate solutions containing Ca. 2+ Mg 2+ CO3 2- Na + SO4 2- Cl - High-salinity wastewater, separated to obtain Ca-free 2+ Mg 2+ NaOH solution and acidic water.

[0003] Existing technologies primarily employ extraction and adsorption for lithium extraction. However, extraction suffers from drawbacks such as long processes and secondary pollution, while adsorption is limited by competitive adsorption and its limited capacity. Some methods address the challenge of lithium extraction from high-magnesium-to-lithium ratio brine in salt lakes by separating lithium ions and magnesium ions during the extraction process. However, current selective electrodialysis (SEE) devices still exhibit problems such as low separation rates and low current efficiency. On one hand, during operation, contaminants in the treatment solution often cause a sharp drop in current efficiency. Alternatively, prolonged operation of the selective ion exchange membrane can lead to the formation of Mg(OH)₂ colloidal precipitates in the cathode chamber when magnesium ions are present in the catholyte. These precipitates adhere to the cathode-side membrane or cathode plate, causing fouling or scaling, reducing separation selectivity, and increasing operating power consumption. On the other hand, SEE also enriches and concentrates ions while separating monovalent ions. During this process, the severe back migration of concentrated ions further reduces current efficiency. Summary of the Invention

[0004] (a) Technical problems to be solved To address the aforementioned problems in the prior art, this invention provides a selective electrodialysis device and its application, which can efficiently separate monovalent and polyvalent ions, and the device operates stably with high separation rate and current efficiency.

[0005] (II) Technical Solution To achieve the above objectives, the main technical solutions adopted by the present invention include: A selective electrodialysis device includes an electrodialysis cell with an anode and a cathode on opposite sides. A cation exchange membrane and an anion exchange membrane are sequentially arranged between the anode and the cathode. The cation exchange membrane is based on a sulfonated polybenzimidazole membrane coated with a porous micro / nano material, sodium polystyrene sulfonate, and the side of the cation exchange membrane facing the anode is coated with a protective layer containing polydiphenylpiperidine. The anion exchange membrane is based on a quaternary ammonium polysulfone or polyethersulfone membrane coated with polydimethyldiallyl ammonium chloride.

[0006] In the selective electrodialysis device described above, preferably, the porous micro / nanomaterial is prepared by dispersing a metal hydrochloride and tetra(4-pyridinylbiphenyl)ethylene in N,N-dimethylformamide at a mass ratio of 1-3:1, subjecting them to ultrasonication for 10-20 minutes, and then reacting them at 120-150°C for 60-90 hours. The metal hydrochloride is zinc chloride, nickel chloride, or copper chloride.

[0007] Furthermore, the mixture of the metal hydrochloride and tetra(4-pyridinebiphenyl)ethylene is dispersed in N,N-dimethylformamide at a concentration of 5-10 mg / mL. When the amount of N,N-dimethylformamide is too small, the system viscosity is high, and it is difficult to disperse the metal hydrochloride and tetra(4-pyridinebiphenyl)ethylene evenly (even with ultrasonic treatment), which may lead to excessively high local concentrations and uneven products. When the amount of N,N-dimethylformamide is too large, the reactant concentration is too low, which will reduce the reaction rate and may even inhibit the coordination reaction (coordination between metal ions and pyridine groups) due to the dilution effect, resulting in a decrease in yield. Therefore, it is preferable that the mixture of metal hydrochloride and tetra(4-pyridinebiphenyl)ethylene is in N,N-dimethylformamide at a mass concentration of 5-10 mg / mL.

[0008] In the selective electrodialysis device described above, preferably, the concentration of sodium polystyrene sulfonate coated in the cation exchange membrane is 10~30 g / L; and the concentration of polydimethyldiallyl ammonium chloride coated in the anion exchange membrane is 15~25 g / L.

[0009] In this invention, sodium polystyrene sulfonate with a concentration of 10-30 g / L is used to effectively increase the charge density of the cation exchange membrane, promote the rapid migration of ions under the action of an electric field, and improve the ion transport rate; the anion exchange membrane contains 15-25 g / L of polydimethyldiallylammonium chloride, which can effectively increase the charge density, thereby improving the ion transport rate.

[0010] The porous micro- and nanomaterials added in this invention can further adsorb or mineralize residual pollutants or degraded small molecule organic matter.

[0011] In the selective electrodialysis apparatus described above, preferably, the side of the cation exchange membrane facing the anode is coated with a cation protective layer, which is polydiphenylpiperidine containing an organic framework catalyst material A.

[0012] Furthermore, the cation protective layer is coated with a dichloromethane solution with a concentration of 0.5~2 mol / L in the form of polydiphenylpiperidine, wherein the amount of organic framework catalyst A is 5~15% of the polydiphenylpiperidine.

[0013] Furthermore, the organic framework catalytic material A is prepared by adding a mixture of 2,4-dicarboxymethyl phloroglucinol and diaminobenzenesulfonic acid in a molar ratio of 1:1.2~1.6 to a mixture of N,N-dimethylformamide and mesitylene. Then, TiO2 nanoparticles with deposited noble metals are dispersed in the mixture, and after sonication for 15~40 min, the mixture is reacted at 110~140℃ for 40~60 h to obtain the product. The noble metals are Pt, Au, Rh, etc.

[0014] The mixture of N,N-dimethylformamide and mesitylene was prepared at a volume ratio of 1:4; the concentrations of 2,4-dicarboxymethyl phloroglucinol and diaminobenzenesulfonic acid in the mixture were 0.1 mol / L and 0.12~0.16 mol / L, respectively; the mass percentage of TiO2 nanoparticles deposited with noble metals in the mixture was 2~5%; and the noble metals accounted for 0.5~10% of the mass of the TiO2 nanoparticles.

[0015] In the method described above, preferably, the side of the anion exchange membrane facing the anode is coated with a polystyrene protective layer containing an organic framework catalyst material B.

[0016] The organic framework catalytic material B is prepared by adding a mixture of 2,4-dicarboxymethyl phloroglucinol and p-phenylenediamine in a molar ratio of 1:1.2~1.6 to a mixture of N,N-dimethylformamide and mesitylene. Then, TiO2 nanoparticles with deposited noble metals are dispersed in the mixture. After sonication for 15~45 min, the mixture is reacted at 120~150℃ for 40~60 h.

[0017] In the selective electrodialysis apparatus described above, preferably, a barrier layer is provided on the side of the cation exchange membrane and the anion exchange membrane facing the cathode. The barrier layer is obtained by coating and drying with a petroleum ether solution containing N-methyl-4-piperidinone and 4-trifluoromethylbiphenyl in a molar ratio of 1:1 to 1.4, wherein the concentration of N-methyl-4-piperidinone is 0.5 to 3 mol / L.

[0018] In the selective electrodialysis device described above, preferably, a group of cation exchange membranes, anion exchange membranes, cation exchange membranes, and anion exchange membranes arranged in the order from anode to cathode is called an electrodialysis unit, and ≥1 dialysis unit is provided between the anode plate and the cathode plate.

[0019] In the selective electrodialysis device described above, preferably, an electrode membrane is provided between the cation exchange membrane and the anode, and an electrode membrane is provided between the anion exchange membrane and the cathode. A partition or mesh is provided between any adjacent cation exchange membrane and anion exchange membrane.

[0020] Furthermore, the electrode membrane is a quaternized polyphenylene ether membrane. Using quaternized polyphenylene ether can prevent cations from entering the electrode chamber and causing scale formation in the electrode water, thus affecting the electrode efficiency.

[0021] In the selective electrodialysis apparatus described above, preferably, an anode chamber is formed between the anode and the electrode membrane near the anode, and a chlorine absorber is also provided in the anode chamber.

[0022] In a preferred embodiment, the selective electrodialysis device further includes a pre-filter located at the front end of the electrodialysis device, i.e., the material enters the electrodialysis device after being processed by the pre-filter, and the filter membrane of the pre-filter is a polyolefin membrane containing adsorbent material.

[0023] Furthermore, the adsorbent material is prepared by reacting tetra-(4-aminophenyl)ethylene (6~10 mol / L) and 2,6-divinylnaphthalene in a molar ratio of 4:1 in a solution of toluene and ethyl acetate (volume ratio of 3:1) for 48~72 h, followed by rinsing and drying.

[0024] In the selective electrodialysis device described above, preferably, multiple sets of cation exchange membranes, separators or meshes, anion exchange membranes, and separators or meshes are provided, arranged alternately in this order. Providing multiple sets of cation exchange membranes and anion exchange membranes can increase the throughput per unit time.

[0025] The selective electrodialysis device described above is used in the separation of lithium and magnesium ions. Specifically, after the solution containing lithium and magnesium ions is treated by the selective electrodialysis device, the lithium ions are enriched in the concentrated liquid chamber formed by the partitions or meshes on the side of the cation exchange membrane and / or anion exchange membrane with protective layers, while the magnesium ions are blocked in the dilute liquid chamber formed by the partitions or meshes on the side of the cation exchange membrane and / or anion exchange membrane with barrier layers, thereby separating the magnesium ions from the lithium ions.

[0026] Specifically, the cation exchange membrane and anion exchange membrane are alternately separated into a concentrated liquid chamber and a dilute liquid chamber by partitions or meshes. After the brine from the salt lake is treated by a selective electrodialysis device, lithium ions are enriched in the concentrated liquid chamber, while magnesium ions are blocked in the dilute liquid chamber, thereby achieving the separation and concentration of lithium ions.

[0027] (III) Beneficial Effects The beneficial effects of this invention are: This invention provides a selective electrodialysis device that increases the membrane charge density by functionalizing the ion exchange membrane, promoting rapid ion migration under an electric field and improving the ion transfer rate. Simultaneously, it incorporates porous micro / nano materials to adsorb and mineralize residual small-molecule organic pollutants, inhibiting their migration into the membrane and preventing fouling. Furthermore, the protective layer of the cation exchange membrane contains polydiphenylpiperidine, which strongly repels multivalent cations such as magnesium, weakening their interaction with monovalent cations such as lithium. This achieves effective retention of multivalent cations without reducing the transport rate of monovalent cations.

[0028] The present invention provides a selective electrodialysis device in which a protective layer is provided between the cation exchange membrane and the anion exchange membrane. The organic framework catalytic material in the protective layer adsorbs and catalytically degrades organic pollutants, effectively solving the problems of reduced separation efficiency and increased power consumption caused by organic pollution during device operation. In addition, the barrier layer of the cation exchange membrane and the anion exchange membrane effectively inhibits the reverse migration of ions when the solution concentration in the concentrate chamber is high, thereby improving the current efficiency and monovalent / polyvalent ion separation rate of the selective electrodialysis device.

[0029] The present invention provides a selective electrodialysis device that can be used to efficiently separate monovalent ions such as lithium ions and sodium ions and polyvalent ions such as magnesium ions, manganese ions, ferrous ions and ferric ions. The device operates stably and the current efficiency is improved by about 30%. Attached Figure Description

[0030] Figure 1 This is a schematic diagram of the structure of a preferred selective electrodialysis device of the present invention.

[0031] Figure 2 This is a schematic diagram of a preferred selective electrodialysis device in Embodiment 1 of the present invention.

[0032] [Explanation of Labels in the Attached Image] 1: Electrodialysis cell; 11: Feed solution; 12: Acceptable solution; 13: Concentrated solution; 14: Diluted solution; 2: Anode; 3: Cathode; 4: Cation exchange membrane; 5: Anion exchange membrane; 6: Partition or mesh; 7: Polar film. Detailed Implementation

[0033] This invention provides a selective electrodialysis device, the structural schematic of which is shown in Figure 1. It includes an electrodialysis tank 1, an anode 2 and a cathode 3 respectively provided on both sides of the electrodialysis tank 1, and a cation exchange membrane 4 and an anion exchange membrane 5 sequentially provided between the anode 2 and the cathode 3. The cation exchange membrane 4 is based on a sulfonated polybenzimidazole membrane and coated with a porous micro-nano material, sodium polystyrene sulfonate. The side of the cation exchange membrane facing the anode is coated with a protective layer containing polydiphenylpiperidine. The anion exchange membrane 5 is based on a quaternary ammonium polysulfone or polyethersulfone membrane and its surface is coated with polydimethyldiallyl ammonium chloride.

[0034] The cation exchange membrane is obtained by coating a 10-30 g / L sodium polystyrene sulfonate casting solution onto a sulfonated polybenzimidazole substrate and then drying it. Furthermore, the casting solution contains porous micro / nanomaterials, with the amount of porous micro / nanomaterials accounting for 3-10% of the sodium polystyrene sulfonate. The porous micro / nanomaterials are prepared by dispersing metal (zinc, nickel, copper, etc.) hydrochloride and tetrakis(4-pyridinebiphenyl)ethylene at a mass ratio of 1-3:1 in N,N-dimethylformamide, followed by ultrasonication for 15-30 minutes and reaction at 120-150°C for 60-90 hours. Preferably, the mixture of metal hydrochloride and tetrakis(4-pyridinebiphenyl)ethylene has a mass concentration of 5-10 mg / mL in N,N-dimethylformamide.

[0035] Extensive experimental studies have shown that coating the cation exchange membrane with sodium polystyrene sulfonate increases the charge density, promotes rapid ion migration under an electric field, and improves the ion transfer rate. Excessive concentration affects the coating effect, while insufficient concentration does not significantly increase the charge density. Therefore, a sodium polystyrene sulfonate concentration of 10–30 g / L is preferred. The porous micro / nanomaterials can further adsorb or mineralize residual pollutants or degraded small-molecule organic matter. The amount of porous micro / nanomaterials used is 3–10% of the sodium polystyrene sulfonate.

[0036] The cation exchange membrane has a protective layer on the side facing the anode, which is a cation protective layer. This cation protective layer is polybiphenylpiperidine containing organic framework catalyst A. Organic framework catalyst A is prepared by adding 2,4-dicarboxymethyl phloroglucinol and diaminobenzenesulfonic acid (molar ratio 1:1.2~1.6) to a mixture of N,N-dimethylformamide and mesitylene (volume ratio 1:4). Then, TiO2 nanoparticles deposited with noble metals such as Pt, Au, and Rh are dispersed in the mixture. After sonication for 15~40 min, the mixture is reacted at 110~140℃ for 40~60 h. TiO2 nanoparticles containing noble metals such as Pt, Au, and Rh are obtained by adding TiO2 nanoparticles to a noble metal salt solution and stirring for several hours, drying, and then calcining at 300-400℃ for 4-6 hours under an inert gas. The mass percentage of TiO2 nanoparticles deposited with noble metals in the mixture is 2-5%, and the noble metals account for 0.5-10% of the mass of TiO2.

[0037] The preferred amount of organic framework catalyst A is 5-15% of polydiphenylpiperidine, wherein the concentration of polydiphenylpiperidine is 0.5-2 mol / L dissolved in dichloromethane solution.

[0038] This invention employs polydiphenylpiperidine, which, being positively charged, strongly repels multivalent cations such as magnesium while weakening their interaction with monovalent cations such as lithium. This achieves effective retention of multivalent cations without reducing the transport rate of monovalent cations. Simultaneously, the organic framework catalyst A adsorbs and catalytically degrades organic pollutants, effectively solving the problems of reduced separation efficiency and increased power consumption caused by organic pollution during device operation. Furthermore, the sulfonic acid groups of the organic framework catalyst A have a stronger electrostatic effect on multivalent cations, pre-adsorbing and limiting the transport of multivalent ions before selective separation.

[0039] The anion exchange membrane uses quaternized polysulfone or polyethersulfone membrane as the substrate and is coated with polydimethyldiallyl ammonium chloride containing 15~25 g / L, which can effectively increase the charge density and thus improve the ion transport rate.

[0040] The anion exchange membrane has a protective layer on the side facing the anode, i.e., the side near the dilute chamber. This protective layer contains polystyrene as an organic framework catalyst material B. The organic framework catalyst material B is prepared by adding a mixture of 2,4-dicarboxymethyl phloroglucinol and p-phenylenediamine in a molar ratio of 1:1.2~1.6 to a mixture of N,N-dimethylformamide and mesitylene in a volume ratio of 1:4. Then, TiO2 nanoparticles (2~5 wt%) deposited with noble metals such as Pt, Au, and Rh are dispersed in the mixture (noble metals account for 0.5~10% of the TiO2 mass). After sonication for 0.5 h, the mixture is reacted at 110~140℃ for 60 h.

[0041] By adding organic framework catalytic material B, organic pollutants can be adsorbed and catalytically degraded, preventing the anion exchange membrane from being contaminated by organic matter during operation.

[0042] A barrier layer is coated on the side of the cation exchange membrane facing the cathode and the side of the anion exchange membrane facing the anode, i.e. the side near the concentrate chamber. The barrier layer is obtained by coating with a petroleum ether solution of a mixture of N-methyl-4-piperidinone and 4-trifluoromethylbiphenyl in a molar ratio of 1:1~1.4 and then drying. This barrier layer effectively inhibits the reverse migration of ions when the solution concentration in the concentrate chamber is high. The concentration of N-methyl-4-piperidinone is 0.5~3 mol / L.

[0043] The optimal molar ratio is 1:1.2 for a petroleum ether solution of N-methyl-4-piperidinone and 4-trifluoromethylbiphenyl, wherein the concentration of N-methyl-4-piperidinone is 1.5 mol / L. A chlorine absorber is installed in the anode chamber. The chlorine absorber controls chlorine escape, achieving safe treatment and resource recovery.

[0044] The selective electrodialysis device is equipped with a pre-filter, which uses a polyolefin membrane doped with adsorbent material. The adsorbent material is prepared by reacting a mixture of tetra-(4-aminophenyl)ethylene (6~10 mol / L) and 2,6-divinylnaphthalene in a molar ratio of 4:1 with a toluene and ethyl acetate solution in a volume ratio of 3:1 for 48~72 h, followed by rinsing and drying.

[0045] After being treated by the pre-filter, suspended solids, solid impurities, and large molecular organic matter in the influent are effectively blocked, ensuring the normal operation of the selective electrodialysis device.

[0046] One embodiment of the present invention provides a selective electrodialysis device, comprising an electrodialysis tank, with an anode and a cathode respectively disposed on both sides of the electrodialysis tank, the anode and cathode being used to connect to the positive and negative terminals of a power supply, respectively. Between the anode and cathode, alternatingly arranged are cation exchange membranes, partitions or meshes, anion exchange membranes, partitions or meshes, cation exchange membranes, partitions or meshes, anion exchange membranes, partitions or meshes, ... The partitions or meshes can be made of polypropylene or polypropylene-polyethylene composite material, their function being to form spaces, i.e., compartments, on both sides of the membranes, and also to improve the flow state. The number of pairs of cation exchange membranes and anion exchange membranes is ≥1. The intervals formed by the partitions or meshes between the cation exchange membranes and anion exchange membranes alternately form concentrated liquid compartments and dilute liquid compartments. Electrode membranes are disposed on both the anode and cathode sides, and the electrodes (anode, cathode) and the electrode membranes form electrode compartments. All concentrated liquid compartments can be connected to a single pipe for inlet or outlet, and all dilute liquid compartments can be connected to a single pipe for inlet or outlet. Figure 1 As shown, during operation, the feed solution 11 and the acceptable solution 12 are added to the dilute and concentrated solution chambers of the device through the feed pipe. After operation, the resulting concentrated solution 13 flows out from the concentrated solution chamber through a pipe, and the dilute solution 14 flows out from the dilute solution chamber through a pipe. The electrode film material is quaternary ammonium polyphenylene ether, the anode material can be titanium coated with ruthenium, titanium coated with lead dioxide, or graphite, and the cathode material can be titanium coated with ruthenium, graphite, or stainless steel, etc.

[0047] The present invention also provides an application of a selective electrodialysis device in the separation of lithium and magnesium ions. Specifically, a concentrated liquid chamber and a dilute liquid chamber are formed by a partition or mesh between the cation exchange membrane and the anion exchange membrane. After the brine from the salt lake is treated by the selective electrodialysis device, lithium ions are enriched in the concentrated liquid chamber, while magnesium ions are blocked in the dilute liquid chamber, thereby achieving the separation and concentration of lithium ions.

[0048] To better explain and facilitate understanding of the present invention, a detailed description of the invention is provided below with reference to the accompanying drawings and specific embodiments. While exemplary embodiments of the invention are shown below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a clearer and more thorough understanding of the invention and to fully convey the scope of the invention to those skilled in the art. Unless otherwise specified, all reagents used in the embodiments are of analytical grade or higher and may be commercially available products.

[0049] Example 1

[0050] A selective electrodialysis apparatus, comprising an electrodialysis cell, such as Figure 2 As shown, an anode 2 and a cathode 3 are respectively provided on both sides of the electrodialysis cell 1. The anode 2 is connected to the positive terminal of the power supply, and the cathode 3 is connected to the negative terminal of the power supply. The materials of the anode 2 and the cathode 3 are titanium-coated lead dioxide. Starting from the anode 2 side, a cation exchange membrane 4 is first set, followed by a partition or mesh 6, then an anion exchange membrane 5, then another partition or mesh 6, and so on, forming an alternating arrangement of cation exchange membrane-partition or mesh-anion exchange membrane-partition or mesh-cation exchange membrane until the cathode side. The first and last membranes are both cation exchange membranes 4. In other words, between anode 2 and cathode 3, cation exchange membrane 4, separator or mesh 6, anion exchange membrane 5, separator or mesh 6, cation exchange membrane 4, etc. are alternately arranged in sequence. The interval between cation exchange membrane 4 and anion exchange membrane 5 and cation exchange membrane 4 alternately forms a concentrate chamber, a dilute chamber, and another concentrate chamber. That is, from the anode to the cathode, the sequence is cation exchange membrane, concentrate chamber (with separator or mesh inside), anion exchange membrane, dilute chamber (with separator or mesh inside), cation exchange membrane, concentrate chamber, etc. The separator or mesh is set as a mesh, mainly to provide a cavity, i.e., a compartment, between the anode and cathode membranes. An electrode membrane 7 is set on one side of the anode and cathode. A separator or mesh 6 is also set between the electrode membrane 7 and anode 2 and cathode 3. An electrode compartment is formed between the electrode (anode, cathode) and the electrode membrane. The anode compartment is formed between anode 2 and electrode membrane 7, and the cathode compartment is formed between cathode 3 and electrode membrane 7. The material of electrode membrane 7 is quaternary ammonium polyphenylene ether.

[0051] The cation exchange membrane used was obtained by coating sulfonated polybenzimidazole with a casting solution containing porous micro / nanomaterials and a concentration of 10 g / L sodium polystyrene sulfonate, followed by drying. The casting solution also contained porous micro / nanomaterials, which were prepared by dispersing zinc chloride and tetrakis(4-pyridinylbiphenyl)ethylene at a mass ratio of 2:1 in N,N-dimethylformamide, followed by ultrasonication for 20 minutes and reaction at 120°C for 90 hours. The preparation method specifically includes the following steps: (1) First, soak the sulfonated polybenzimidazole membrane as a base membrane in deionized water for 2 hours to remove surface impurities, and then air dry or use filter paper to absorb the surface moisture.

[0052] (2) Preparation of casting solution: Zinc chloride and tetra(4-pyridinebiphenyl)ethylene were dispersed in N,N-dimethylformamide solvent at a mass ratio of 2:1, wherein the mass concentration of zinc chloride and tetra(4-pyridinebiphenyl)ethylene in N,N-dimethylformamide solvent was 5~10 mg / mL. The ultrasonic power was 300~500W, and after ultrasonication for 20 minutes, the ultrasonic dispersion was reacted at 120℃ for 90h. After the reaction was completed, the mixture was cooled to room temperature, filtered, and washed 3-5 times alternately with N,N-dimethylformamide (DMF) and deionized water (to remove unreacted raw materials and impurities). Then, it was vacuum dried at 60-80℃ for 12 hours to obtain white or light yellow porous micro / nanomaterial powder.

[0053] Weigh 10g of sodium polystyrene sulfonate, add it to 1L of deionized water, stir until completely dissolved to form a transparent PSS solution, then add 0.5g of the porous micro / nano material powder prepared above, stir evenly, and sonicate again for 10-15 minutes to ensure that the material is evenly dispersed in the casting solution to form a stable suspension casting solution.

[0054] Slowly immerse the base film into the casting solution and let it stand for 10-30 seconds to allow the casting solution to adhere evenly to the surface of the base film. Then slowly remove it and hang it vertically to drain excess liquid.

[0055] (3) Place the coated film in an oven and dry it at 60~80℃ for 2-4 hours (low temperature and slow drying to avoid rapid evaporation of solvent that could cause cracking on the film surface) until the film is completely dry and a uniform composite film layer is formed.

[0056] (4) After drying, the membrane is soaked in deionized water for 12 hours to remove unreacted PSS and residual solvent, thus obtaining a cation exchange membrane coated with sodium polystyrene sulfonate containing porous micro-nano materials (sulfonic acid groups dissociate in water, giving the membrane selective permeability to cations).

[0057] The surface of the cation exchange membrane near the desalination chamber is also coated with a polydiphenylpiperidine protective layer containing organic framework catalyst A. Organic framework catalyst A is prepared by adding a mixture of 2,4-dicarboxymethyl phloroglucinol and diaminobenzenesulfonic acid (molar ratio 1:1.4) to a mixture of N,N-dimethylformamide and mesitylene (volume ratio 1:4), where the concentration of 2,4-dicarboxymethyl phloroglucinol in the mixture is 0.1 mol / L and the concentration of diaminobenzenesulfonic acid is 0.14 mol / L. Then, TiO2 nanoparticles deposited with Pt are dispersed in the mixture at a mass concentration of 2%, sonicated for 0.5 h, and reacted at 120℃ for 60 h. The Pt-deposited TiO2 nanoparticles can be prepared by chemical deposition or impregnation reduction. Specifically, TiO2 nanoparticles are added to a noble metal salt solution and stirred for several hours, dried, and then calcined at 300-400℃ for 4-6 h under an inert gas atmosphere. The mass percentage of TiO2 nanoparticles deposited with noble metals in the mixture is 2 wt%, and the noble metal Pt accounts for 5 wt% of TiO2. A polydiphenylpiperidine protective layer of framework catalyst material A is sprayed onto one side of the cation exchange membrane prepared above. The polydiphenylpiperidine content is 0.5~2 mol / L dichloromethane solution, and the amount of framework catalyst material A is 5~15% of the polydiphenylpiperidine.

[0058] A barrier layer is sprayed onto the other side of the cation exchange membrane. Specifically, the barrier layer is a solution of N-methyl-4-piperidinone and 4-trifluoromethylbiphenyl petroleum ether in a molar ratio of 1:1~1.4, wherein the concentration of N-methyl-4-piperidinone is 1.5 mol / L. The mixture is coated onto the cation exchange membrane and dried at 60°C for 12 h.

[0059] The anion exchange membrane uses quaternized polysulfone as a substrate, with a surface coating containing 25 g / L polydimethyldiallylammonium chloride. The surface of the anion exchange membrane near the dilute chamber is also coated with a polystyrene protective layer containing an organic framework catalyst B. The organic framework catalyst B is prepared by adding 2,4-dicarboxymethyl phloroglucinol and p-phenylenediamine (0.1 mol / L 2,4-dicarboxymethyl phloroglucinol and 0.14 mol / L diaminobenzenesulfonic acid) in a molar ratio of 1:1.4 to a mixture of N,N-dimethylformamide and mesitylene in a volume ratio of 1:4. Then, TiO2 nanoparticles deposited with Au are dispersed in the mixture at a mass concentration of 2-5%. After sonication for 0.5 h, the mixture is reacted at 110 °C for 60 h. The prepared organic framework catalyst B is added to the polystyrene at an amount of 5-10% of the polystyrene mass.

[0060] The other side of the anion exchange membrane is coated with a barrier layer. Specifically, the barrier layer is a solution of N-methyl-4-piperidinone and 4-trifluoromethylbiphenyl petroleum ether in a molar ratio of 1:1.2, wherein the concentration of N-methyl-4-piperidinone is 1.5 mol / L. This mixture is coated onto the anion exchange membrane and dried at 60°C for 12 h.

[0061] The cation exchange membrane and anion exchange membrane coated with a barrier layer are placed on the side of the concentrate chamber.

[0062] A chlorine absorber is installed in the anode chamber. The selective electrodialysis device is equipped with a pre-filter, which uses a polyolefin membrane containing adsorbent material. The adsorbent material is prepared by reacting tetra-(4-aminophenyl)ethylene and 2,6-divinylnaphthalene in a toluene and ethyl acetate solution for 48 hours, followed by rinsing and drying.

[0063] Specifically, the pre-filter is prepared by using a polyolefin membrane as a substrate, reacting a mixture of tetra-(4-aminophenyl)ethylene (8 mol / L) and 2,6-divinylnaphthalene (2 mol / L) in a toluene and ethyl acetate solution at a volume ratio of 3:1 for 48 h, then rinsing with ethanol and drying at 80 °C.

[0064] The pre-filter is installed before the electrodialysis unit. It is a pre-filter, meaning that the permeate water enters the electrodialysis unit for monovalent and multivalent ion separation after being treated by the pre-filter.

[0065] In application, the device of the present invention involves adding a liquid containing 400 mg / L lithium ions and 12000 mg / L magnesium ions to the dilute and concentrated liquid chambers of the electrolytic cell of the selective electrodialysis device described above. A 2% sodium sulfate solution is added to both electrode chambers. The power supply is then connected, and the current density is set to 300 A / m. 2 The sample was analyzed after 60 minutes. It is used for ion chromatography to measure ion concentration, and the permeation rate is calculated based on the concentration difference.

[0066] The selective electrodialysis device was tested for the separation rate of lithium and magnesium ions. The initial water sample contained 400 mg / L of lithium ions and 12000 mg / L of magnesium ions, with a current density of 300 A / m. 2 The membrane flow rate was 4 cm / s. The lithium-magnesium separation rate was calculated as the ratio of lithium permeation from the dilute chamber to the concentrate chamber to magnesium permeation from the dilute chamber to the concentrate chamber. The current efficiency was calculated as: (number of moles of ions permeated) × Faraday constant / (charge) × 100%. Test results: lithium-magnesium separation rate 46.9%, current efficiency 88.3%.

[0067] Example 2

[0068] In this embodiment, the provided selective electrodialysis device includes an electrodialysis cell with an anode and a cathode respectively disposed on both sides of the cell. The anode and cathode are made of graphite. A cation exchange membrane, a partition or mesh, an anion exchange membrane, a partition or mesh, and another cation exchange membrane are alternately disposed between the anode and cathode. An electrode membrane is disposed on the side of both the anode and cathode electrodes near the partition or mesh. An anode chamber is formed between the anode electrode and the electrode membrane, and a cathode chamber is formed between the cathode electrode and the electrode membrane. The electrode membrane is made of quaternary ammonium polyphenylene ether.

[0069] The cation exchange membrane used was obtained by coating sulfonated polybenzimidazole with a 20 g / L sodium polystyrene sulfonate casting solution and drying it. The casting solution also contained porous micro- and nanomaterials. The membrane was prepared by dispersing nickel chloride and tetra(4-pyridinebiphenyl)ethylene in N,N-dimethylformamide at a mass ratio of 3:1, followed by ultrasonication for 20 minutes and reaction at 150°C for 75 hours.

[0070] The cation exchange membrane used is covered with a polydiphenylpiperidine protective layer containing organic framework catalyst material A on the surface of the desalination chamber side, and a barrier layer is coated on the other side surface.

[0071] Specifically, the preparation of the cation exchange membrane is the same as in Example 1, except that: the mixture of 2,4-dicarboxymethyl phloroglucinol and diaminobenzenesulfonic acid in a molar ratio of 1:1.2 in the preparation method of organic framework catalytic material A is added to a mixture of N,N-dimethylformamide and mesitylene in a volume ratio of 1:4, and then TiO2 nanoparticles deposited with Au are dispersed in the mixture. After sonication for 0.5 h, the mixture is reacted at 110 °C for 60 h to obtain the final product. The mass percentage of the TiO2 nanoparticles deposited with noble metal in the mixture is 5 wt%, and the noble metal Au accounts for 0.5 wt% of the TiO2.

[0072] A barrier layer is sprayed onto the other side of the cation exchange membrane. Specifically, the barrier layer is made by dissolving N-methyl-4-piperidinone and 4-trifluoromethylbiphenyl in a petroleum ether solution at a molar ratio of 1:1.2, wherein the concentration of N-methyl-4-piperidinone is 1.5 mol / L. The mixture is then coated onto the cation exchange membrane and dried at 60°C for 12 h.

[0073] The anion exchange membrane is made of quaternized polyethersulfone and coated with a 20 g / L polydimethyldiallylammonium chloride solution. The surface of the anion exchange membrane near the dilute chamber is also coated with a polystyrene protective layer containing an organic framework catalyst B. The organic framework catalyst B is prepared by adding 2,4-dicarboxymethyl phloroglucinol and p-phenylenediamine (molar ratio 1:1.6) to a mixture of N,N-dimethylformamide and mesitylene. Then, Pt-deposited TiO2 nanoparticles are dispersed in the mixture, and the mixture is sonicated for 0.5 h and then reacted at 130 °C for 60 h. The mass percentage of the TiO2 nanoparticles deposited with the noble metal in the mixture is 5 wt%, and the noble metal Pt accounts for 0.5 wt% of the TiO2.

[0074] The anion exchange membrane is prepared by using quaternized polyethersulfone as a substrate and coating the surface with 20 g / L polydimethyldiallyl ammonium chloride.

[0075] The cation exchange membrane and anion exchange membrane are coated with a barrier layer on the side of the concentrate chamber. The barrier layer is obtained by coating with a petroleum ether solution of N-methyl-4-piperidinone and 4-trifluoromethylbiphenyl (molar ratio 1:1.2) and then drying.

[0076] A chlorine absorber is installed in the anode chamber. The selective electrodialysis device is equipped with a pre-filter, which uses a polyolefin membrane containing adsorbent material. The adsorbent material is prepared by reacting a mixture of tetra-(4-aminophenyl)ethylene (8 mol / L) and 2,6-divinylnaphthalene (2 mol / L) in a toluene and ethyl acetate solution for 60 h, followed by rinsing with ethanol and drying at 80 °C.

[0077] The selective electrodialysis device was tested for its effectiveness in separating liquids containing lithium and magnesium ions, following the procedure described in Example 1.

[0078] The selective electrodialysis device of this embodiment was tested for its separation rate of lithium ions and magnesium ions. The initial water sample contained 400 mg / L of lithium ions and 12000 mg / L of magnesium ions, with a current density of 300 A / m. 2 The membrane flow rate was 4 cm / s. The test results were: lithium-magnesium separation rate 48.3% and current efficiency 87.6%.

[0079] Example 3

[0080] In this embodiment, the selective electrodialysis device includes an electrodialysis cell with the same structure as in Embodiment 1. An anode and a cathode are respectively provided on both sides of the electrodialysis cell. Between the anode and cathode, a cation exchange membrane, a partition or mesh, an anion exchange membrane, another partition or mesh, and another cation exchange membrane are alternately arranged in sequence. The intervals between the cation exchange membrane and the anion exchange membrane alternately form a concentrate chamber and a dilute chamber. An electrode membrane is provided on one side of both the anode and the cathode. The electrodes (anode and cathode) and the electrode membrane form an electrode chamber. The electrode membrane is made of quaternary ammonium polyphenylene ether.

[0081] The preparation method of the cation exchange membrane is the same as in Example 1, except that: it is obtained by coating sulfonated polybenzimidazole with a 30 g / L sodium polystyrene sulfonate casting solution and drying it. The casting solution also contains porous micro- and nanomaterials. The membrane is prepared by dispersing a mixture of copper chloride and tetra(4-pyridinebiphenyl)ethylene in a mass ratio of 1:1 in N,N-dimethylformamide, sonicating for 20 minutes, and then reacting at 130°C for 60 hours.

[0082] The cation exchange membrane is coated with a protective layer of polydiphenylpiperidine containing organic framework catalyst material A on the surface of the dilute chamber side, and a barrier layer is coated on the other side surface. Specifically, the preparation of the cation exchange membrane is the same as in Example 1, except that: in the preparation method of organic framework catalyst material A, a mixture of 2,4-dicarboxymethyl phloroglucinol and diaminobenzenesulfonic acid in a molar ratio of 1:1.6 is added to a mixture of N,N-dimethylformamide and mesitylene in a volume ratio of 1~4. Then, TiO2 nanoparticles (3%) deposited with Rh (10%) are dispersed in the mixture, and after sonication for 0.5 h, the mixture is reacted at 140 °C for 60 h to obtain the final product. The mass percentage of the TiO2 nanoparticles deposited with noble metal in the mixture is 3 wt%, and the noble metal Rh accounts for 10 wt% of the TiO2.

[0083] The anion exchange membrane is made of quaternized polysulfone and coated with 15 g / L polydimethyldiallylammonium chloride. The surface of the anion exchange membrane near the dilute chamber is also coated with a polystyrene protective layer containing organic framework catalyst B. Organic framework catalyst B is prepared by adding a mixture of 0.1 mol / L 2,4-dicarboxymethyl phloroglucinol and p-phenylenediamine in a molar ratio of 1:1.5 to a mixture of N,N-dimethylformamide and mesitylene in a volume ratio of 1:4. Then, TiO2 nanoparticles (3%) deposited with Rh (10%) are dispersed in the mixture. After sonication for 0.5 h, the mixture is reacted at 140 °C for 60 h. The mass percentage of the TiO2 nanoparticles deposited with noble metal in the mixture is 3 wt%, and the noble metal Rh accounts for 10 wt% of the TiO2.

[0084] The cation exchange membrane and anion exchange membrane are coated with a barrier layer on the surface of the concentrate chamber side. This layer is prepared by coating with a petroleum ether solution of N-methyl-4-piperidinone and 4-trifluoromethylbiphenyl (molar ratio 1:1.2) and then drying, with the N-methyl-4-piperidinone concentration being 1.5 mol / L. A chlorine absorber is installed in the anode chamber. The selective electrodialysis device is equipped with a pre-filter, which uses a polyolefin membrane containing adsorbent material. The adsorbent material is prepared by reacting tetra-(4-aminophenyl)ethylene (8 mol / L) and 2,6-divinylnaphthalene (2 mol / L) in a toluene and ethyl acetate solution at a volume ratio of 3:1 for 72 h, followed by rinsing with ethanol and drying at 80°C.

[0085] Following the procedure described in Example 1, the effectiveness of the selective electrodialysis device in separating liquids containing lithium and magnesium ions was tested. The separation rate of lithium and magnesium ions by the selective electrodialysis device in this example was tested with an initial water sample containing 400 mg / L lithium ions and 12000 mg / L magnesium ions, at a current density of 300 A / m³. 2 The membrane flow rate was 4 cm / s. The test results were: lithium-magnesium separation rate 47.5% and current efficiency 89.1%.

[0086] Example 4

[0087] In this embodiment, the selective electrodialysis device includes an electrodialysis tank, with an anode and a cathode respectively provided on both sides of the electrodialysis tank. The anode is connected to the positive terminal of the power supply, and the cathode is connected to the negative terminal of the power supply. The materials of the anode and cathode are titanium-coated lead dioxide. A cation exchange membrane, a partition or mesh, an anion exchange membrane, a partition or mesh, a cation exchange membrane, etc. are alternately arranged between the anode and the cathode in sequence, with a total of 10 cation exchange membranes and 10 anion exchange membranes. The interval between the cation exchange membranes and anion exchange membranes alternately forms a concentrate chamber and a dilute chamber. An electrode membrane is provided on one side of both the anode and the cathode. The electrodes (anode and cathode) and the electrode membranes form an electrode chamber. The material of the electrode membrane is quaternary ammonium polyphenylene ether.

[0088] The specific preparation methods for cation exchange membranes and anion exchange membranes are the same as in Example 1, except that: the cation exchange membrane used is obtained by coating sulfonated polybenzimidazole with a 25 g / L sodium polystyrene sulfonate casting solution and drying it. The casting solution also contains porous micro- and nano-materials. The porous micro- and nano-materials are prepared by dispersing 6 g / L zinc chloride and tetrakis(4-pyridinylbiphenyl)ethylene at a mass ratio of 1.5:1 in N,N-dimethylformamide, sonicating for 20 minutes, and then reacting at 140°C for 60 hours.

[0089] The surface of the cation exchange membrane on the side near the desalination chamber is also covered with a polydiphenylpiperidine protective layer containing organic framework catalyst material A. The organic framework catalyst material A is prepared by adding a mixture of 2,4-dicarboxymethyl phloroglucinol and diaminobenzenesulfonic acid in a molar ratio of 1:1.3 to a mixture of N,N-dimethylformamide and mesitylene in a volume ratio of 1:4, wherein the concentration of 2,4-dicarboxymethyl phloroglucinol in the mixture is 0.1 mol / L. Then, TiO2 nanoparticles (3 wt%) with Pt (5 wt%) are dispersed in the mixture, and after sonication for 0.5 h, the mixture is reacted at 120 °C for 60 h to obtain the final product.

[0090] The anion exchange membrane is made of quaternized polysulfone and coated with a 20 g / L polydimethyldiallylammonium chloride solution. The surface of the anion exchange membrane near the dilute chamber is also coated with a polystyrene protective layer containing an organic framework catalyst B. The organic framework catalyst B is prepared by adding a mixture of 0.1 mol / L 2,4-dicarboxymethyl phloroglucinol and p-phenylenediamine in a molar ratio of 1:1.2 to a mixture of N,N-dimethylformamide and mesitylene in a volume ratio of 1:4. Then, TiO2 nanoparticles (3 wt%) with Pt (5 wt%) are dispersed in the mixture. After sonication for 0.5 h, the mixture is reacted at 120 °C for 60 h.

[0091] The cation exchange membrane and anion exchange membrane are coated with a barrier layer on the side of the concentrate chamber. The barrier layer is obtained by coating with a petroleum ether solution of N-methyl-4-piperidinone and 4-trifluoromethylbiphenyl (molar ratio 1:1.2) and then drying.

[0092] A chlorine absorber is installed in the anode chamber. The selective electrodialysis device is equipped with a pre-filter, which uses a polyolefin membrane containing adsorbent material. The adsorbent material is prepared by reacting tetra-(4-aminophenyl)ethylene (8 mol / L) and 2,6-divinylnaphthalene (2 mol / L) in a toluene and ethyl acetate solution with a volume ratio of 3:1 for 65 h, followed by rinsing and drying.

[0093] Following the procedure described in Example 1, the effectiveness of the selective electrodialysis device in separating liquids containing lithium and magnesium ions was tested. The separation rate of lithium and magnesium ions by the selective electrodialysis device in this example was tested with an initial water sample containing 400 mg / L lithium ions and 12000 mg / L magnesium ions, at a current density of 300 A / m³. 2 The membrane flow rate was 4 cm / s. The test results were: lithium-magnesium separation rate 47.2% and current efficiency 88.7%.

[0094] Comparative Example 1 The selective electrodialysis device in this comparative example is identical to that in Example 1, except that the sodium polystyrene sulfonate coated on the cation exchange membrane does not contain porous micro / nano materials.

[0095] The preparation method of the sodium polystyrene sulfonate coated on the cation exchange membrane does not contain porous micro-nano materials, including (1) first soaking the sulfonated polybenzimidazole membrane as the base membrane in deionized water for 2 hours to remove surface impurities, and then drying it or absorbing the surface moisture with filter paper.

[0096] (2) Weigh 10g of sodium polystyrene sulfonate, add it to 1L of deionized water, stir until completely dissolved to form a transparent PSS solution as the casting solution, slowly immerse the base film in the casting solution, let it stand for 30 seconds to allow the casting solution to adhere evenly to the surface of the base film, and then slowly remove it and hang it vertically to drain excess liquid.

[0097] (3) Place the coated film in an oven and dry it at 70°C for 3 hours until the film is completely dry and a uniform composite film layer is formed.

[0098] (4) The dried membrane was soaked in deionized water for 12 hours to remove unreacted PSS and residual solvent, thus obtaining a cation exchange membrane coated with sodium polystyrene sulfonate. The selective electrodialysis device of this comparative example was tested for lithium and magnesium ion separation rates using the same method as in Example 1. The initial water sample contained 400 mg / L lithium ions and 12000 mg / L magnesium ions, with a current density of 300 A / m³. 2 The membrane flow rate was 4 cm / s. The test results were: lithium-magnesium separation rate 29.2% and current efficiency 67.6%.

[0099] Comparative Example 2 In the selective electrodialysis apparatus of this comparative example, neither the cation exchange membrane nor the anion exchange membrane has a protective layer on the surface of the dilute liquid chamber side; otherwise, it is the same as in Example 1.

[0100] The selective electrodialysis device was tested for the separation rate of lithium and magnesium ions. The initial water sample contained 400 mg / L of lithium ions and 12000 mg / L of magnesium ions, with a current density of 300 A / m. 2 The membrane flow rate was 4 cm / s. The test results were: lithium-magnesium separation rate 23.4% and current efficiency 62.1%.

[0101] Comparative Example 3 In the selective electrodialysis apparatus of this comparative example, neither the cation exchange membrane nor the anion exchange membrane has a barrier layer on the surface of the concentrate chamber side; otherwise, it is the same as in Example 1.

[0102] The selective electrodialysis device was tested for the separation rate of lithium and magnesium ions. The initial water sample contained 400 mg / L of lithium ions and 12000 mg / L of magnesium ions, with a current density of 300 A / m. 2 The membrane flow rate was 4 cm / s. The test results were: lithium-magnesium separation rate 32.1% and current efficiency 60.2%.

[0103] Comparative Example 4 In this comparative example, the selective electrodialysis apparatus, wherein the pre-filter is a polyolefin membrane containing no adsorbent material, is otherwise identical to that in Example 1.

[0104] The selective electrodialysis device was tested for the separation rate of lithium and magnesium ions. The initial water sample contained 400 mg / L of lithium ions and 12000 mg / L of magnesium ions, with a current density of 300 A / m. 2 The membrane flow rate was 5 cm / s. The test results were: lithium-magnesium separation rate 35.5% and current efficiency 66.7%.

[0105] As can be seen from the above, coating the cation exchange membrane with porous micro / nano materials can effectively improve the lithium-magnesium separation rate by 19.7% and the current efficiency by 20%. When both the cation exchange membrane and the anion exchange membrane are equipped with protective layers, the lithium-magnesium separation rate can be improved by 23.5% and the current efficiency by 26.2%. When both the cation exchange membrane and the anion exchange membrane are equipped with barrier layers, the lithium-magnesium separation rate can be improved by 14.8% and the current efficiency by 28.1%. The current filter using a polyolefin membrane containing adsorbent material can improve the lithium-magnesium separation rate by 11.4% and the current efficiency by 21.6% compared to a polyolefin membrane without adsorbent material, demonstrating significant effects.

[0106] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other way. Any person skilled in the art can make changes or modifications to the above-disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A selective electrodialysis device, characterized in that, It includes an electrodialysis cell, with an anode and a cathode respectively on both sides of the electrodialysis cell. A cation exchange membrane and an anion exchange membrane are arranged sequentially between the anode and the cathode. The cation exchange membrane is based on sulfonated polybenzimidazole, and its surface is coated with sodium polystyrene sulfonate containing porous micro and nano materials. The side of the cation exchange membrane facing the anode is coated with a protective layer containing polydiphenylpiperidine. The anion exchange membrane uses quaternized polysulfone or polyethersulfone as a substrate, and its surface is coated with polydimethyldiallylammonium chloride.

2. The selective electrodialysis apparatus as described in claim 1, characterized in that, The porous micro / nanomaterial is prepared by dispersing a metal hydrochloride and tetra(4-pyridinebiphenyl)ethylene in N,N-dimethylformamide at a mass ratio of 1-3:1, subjecting them to ultrasonication for 10-20 minutes, and then reacting them at 120-150°C for 60-90 hours. The metal hydrochloride is zinc chloride, nickel chloride, or copper chloride.

3. The selective electrodialysis apparatus as described in claim 1, characterized in that, The concentration of sodium polystyrene sulfonate coated in the cation exchange membrane is 10~30 g / L; the concentration of polydimethyldiallyl ammonium chloride coated in the anion exchange membrane is 15~25 g / L.

4. The selective electrodialysis apparatus as described in claim 1, characterized in that, The cation exchange membrane is coated with a cation protective layer on the anode-facing side. The cation protective layer is polydiphenylpiperidine containing organic framework catalyst material A. The organic framework catalyst material A is prepared by adding a mixture of 2,4-dicarboxymethyl phloroglucinol and diaminobenzenesulfonic acid in a molar ratio of 1:1.2~1.6 to a mixture of N,N-dimethylformamide and mesitylene. Then, TiO2 nanoparticles with deposited noble metals are dispersed in the mixture. After sonication for 15~40 min, the mixture is reacted at 110~140℃ for 40~60 h. The noble metal is Pt, Au or Rh.

5. The selective electrodialysis apparatus as described in claim 1, characterized in that, The anion exchange membrane is coated with a polystyrene protective layer containing organic framework catalyst material B on the anode side. The organic framework catalyst material B is prepared by adding a mixture of 2,4-dicarboxymethyl phloroglucinol and p-phenylenediamine in a molar ratio of 1:1.2~1.6 to a mixture of N,N-dimethylformamide and mesitylene. Then, TiO2 nanoparticles with deposited noble metals are dispersed in the mixture. After sonication for 15~45 min, the mixture is reacted at 120~150℃ for 40~60 h.

6. The selective electrodialysis apparatus as described in claim 1, characterized in that, The cation exchange membrane and the anion exchange membrane have a barrier layer on the side facing the cathode. The barrier layer is obtained by coating with a petroleum ether solution containing N-methyl-4-piperidinone and 4-trifluoromethylbiphenyl in a molar ratio of 1:1 to 1.4 and then drying it.

7. The selective electrodialysis apparatus as described in claim 1, characterized in that, A set of cation exchange membranes, anion exchange membranes, cation exchange membranes, and anion exchange membranes arranged in the order from anode to cathode is called an electrodialysis unit. There is ≥1 electrodialysis unit between the anode and the cathode.

8. The selective electrodialysis apparatus as described in claim 7, characterized in that, An electrode membrane is provided between the cation exchange membrane and the anode, and an electrode membrane is provided between the anion exchange membrane and the cathode. A partition or mesh is provided between any adjacent cation exchange membrane and anion exchange membrane.

9. The selective electrodialysis apparatus as described in claim 8, characterized in that, The electrode membrane is a quaternized polyphenylene ether membrane; An anode chamber is formed between the anode and the electrode film near the anode, and a chlorine absorber is also provided in the anode chamber.

10. The application of the selective electrodialysis apparatus as described in any one of claims 1-9 in the separation of lithium and magnesium ions.

Citation Information

Patent Citations

  • Monovalent selective bipolar membrane electrodialysis device and method for treating high-salinity wastewater

    CN115448429A

  • Polyvinyl alcohol anion-exchange membrane and preparation method thereof

    CN103252175A

  • Ion exchange membrane with monovalent ion selectivity and preparing method and application thereof

    CN106099147A

  • Multi-membrane stacking electrodialysis system based on modified membranes and chemical salt-containing wastewater treatment method

    CN116102134A

  • Electroactivated film with polymer GEL electrolyte

    WO2009143314A2